A mechanistic investigation of lignin dimer fast pyrolysis from reactive molecular dynamics simulation. Issue 6 (December 2021) - Zhou, Yuling; Dang, Qi; Wu, Yun; Lei, Taoning
Abstract: The investigation of biomass pyrolysis mechanism is crucial for the advancement of pyrolysis-based technology and it is still quite challenging due to the complex nature of lignocellulosic biomass. The application of reactive molecular dynamics simulation offers a powerful strategy to probe more essential information along the reaction process beyond advanced experimental techniques. In this work, the fast pyrolysis process of a lignin dimer, DMPD with representative β-O-4 linkage, is investigated using the ReaxFF method to explore the reaction characteristics, mechanism, and kinetics. The results elucidate that higher temperatures are favorable for the formation of CO, the transformation of guaiacol to catechol, and the breaking of bonds when varying the temperature from 1400 to 2400 K. Guaiacol achieves the highest yield of 13.37% at 2000 K while catechol and CO obtain the highest yield of 6.67% and 8.22% at 2400 K, respectively. Higher heating rates promote the generation of C5-12 products (increased from 70.59% to 78.23%) and the breaking of C-O bond regarding the investigated range of 15.5–170 K/ps. Based upon the time evolution of the reactant and final product distribution under various operating conditions, a first-order kinetic model is derived to calculate the activation energies of C-C, C-H, C-⎔O bonds, and DMPD to be 122.41, 35.18, 52.58, and 52.18 kJ/mol, respectively. A reaction pathway is proposed from the product distribution along the DMPD pyrolysis at 2000 K. The detailed characteristics from ReaxFF simulations enable a better understanding of the complicated pyrolysis mechanism of biomass from a molecular level. Graphical Abstract: ga1 Highlights: The reaction mechanism and kinetic characteristics of DMPD fast pyrolysis were comprehensively investigated using ReaxFF. Higher temperatures favor the production of catechol and guaiacol with highest yields of 6.67% and 13.37%, respectively. Raising the heating rate promotes the generation of C5-12 products from 70.59% to 78.23% and breaking of C-O bonds. A first-order kinetic model is established to calculate the activation energies of DMPD, C-C, C-H, and C-O bonds.